PEUBAHAN BENTUK TARI PIRIANG RANTAK TAPI DI NAGARI PITALAH KABUPATEN TANAH DATAR - Nela Majesti; Indrayuda Indrayuda; Darmawati Darmawati (SENDRATASIK UNP, 2014)
Abstract This article was aimed at describing the changes on the form of Piriang Rantak Tapi dance in Nagari Pitalah Kecamatan Batipuh Kabupaten Tanah Datar. This research applied descriptive methud the data was collected though library study, observation, interview and documentation. The result of the research indicated that Piriang Rantak Tapi dance got changes in 1991. The changes was affected by the social and culture factors. They occurred on the dance form including (a) the structural form of movement, (b) the form of music, (c) custom, (d) properties and (e) time. The second change occure on the place of the show and the third cange was on the events precenting Piriang Rantak Tapi dance, such as in a traditional festival, in a wedding party and some accasions held by the tourism department.   Kata Kunci: Perubahan Bentuk, Tari Piriang Rantak Tapi, Nagari Pitalah.